2021
DOI: 10.1038/s41598-021-91188-1
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady hybrid-nanofluid flow comprising ferrousoxide and CNTs through porous horizontal channel with dilating/squeezing walls

Abstract: The key objective of the present research is to examine the hybrid magnetohydrodynamics (MHD) nanofluid (Carbon-nanotubes and ferrous oxide–water) CNT–Fe3O4/H2 flow into a horizontal parallel channel with thermal radiation through squeezing and dilating porous walls. The parting motion is triggered by the porous walls of the channel. The fluid flow is time-dependent and laminar. The channel is asymmetric and the upper and lower walls are distinct in temperature and are porous. With the combination of nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…The distance between two plates has taken as h(t) = l √ 1 − at; furthemore, the upper plate move towards the lower plate with velocity v = dh dt . We Continuity equation [15]:…”
Section: Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The distance between two plates has taken as h(t) = l √ 1 − at; furthemore, the upper plate move towards the lower plate with velocity v = dh dt . We Continuity equation [15]:…”
Section: Formulationmentioning
confidence: 99%
“…Hayat et al [13] examined the impact of couple stress fluid flow in the presence of the time-dependent magnetic field. Hayat et al both [14,15] used the Buongiorno model of nanofluids, which indirectly tested certain nanoparticles. In the meantime, Salehi et al [16] studied the squeezing hybrid nanofluid which can be formulated by putting the nanomaterial Fe 3 O 4 -MoS 2 in the base fluid water and ethylene glycol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid nanofluids improve the materials’ physical and chemical properties at the same time. As compared to simple nanofluids 30 – 33 , the hybrid nanofluids 34 39 have more effect on the betterment of heat transfer because they have more thermal conductivity and can be molded according to the requirement. Synthetic hybrid nanofluids demonstrate unusual properties that are not presented by individual components.…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al 34 studied the microstructure characteristics of MHD suspended CNT nanofluid flow and noted the Eckert number accelerates the kinetic energy of molecules. An unsteady hybrid nanofluid flow of CNTs has been examined by Bilal et al 35 Later many researchers work in this direction. [36][37][38] The present problem addresses a comparative study on the results, found by a developed algorithm of HAM and Rabin-Karp (RK) method with shooting technique.…”
Section: Introductionmentioning
confidence: 99%